Levetiracetam-induced interstitial lung disease in a patient with advanced lung cancer. (2020) - Sato, Shintaro; Oba, Tomohiro; Ohta, Hiroki; Tsukahara, Yuta; Kida, Gen; Tsumiyama, Emiri; Kusano, Kenji; Nishizawa, Tomotaka; Kawabe, Rie; Yamakawa, Hideaki; Akasaka, Keiichi; Amano, Masako; et al.
Abstract: An 85-year-old woman with antibiotics-resistant pneumonia after surgery for metastatic brain tumor from lung cancer was consulted to our department. Chest CT showed diffuse GGO bilaterally. BALF showed elevated ratios of lymphocytes and CD4/CD8. Tests for bacteria, mycobacteria, and fungi were negative. She improved following levetiracetam discontinuance and systemic corticosteroid administration, and we diagnosed levetiracetam-induced lung injury. Although levetiracetam is widely used, few reports of levetiracetam-induced pneumonia exist. Changes in chest images may occur after levetiracetam administration if patients have multiple risk factors for development of drug-induced interstitial lung disease. Bronchoscopy is useful for differential diagnosis if new lung lesions appear after starting levetiracetam.